Advocacy of Gerakan Aksesibilitas Umum Nasional for Persons with Disabilities in Using Mikrotrans JakLingko Mode of Transportation - Bonpalda, Ginna Glyceria; Ghofur, Abdul (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Mikrotrans is one of the transportation variants of Transjakarta, which is the result of the integration of Transjakarta with JakLingko. This research focuses on the advocacy carried out by Gerakan Aksesibilitas Umum Nasional (GAUN) for people with disabilities in using Mikrotrans, with the object of research being Mikrotrans. This research was conducted with the aim of knowing what advocacy was carried out by GAUN as an organization of persons with disabilities on the use of Mikrotrans for persons with disabilities. The method used in this research is qualitative, with analysis techniques presented by Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion drawing. The novelty of this research can be seen from its research focus, namely advocacy from organizations of persons with disabilities on the use of Mikrotrans for persons with disabilities. This research needs to be done to find answers to the questions in this study. The results showed that GAUN as one of the organizations of persons with disabilities in Indonesia, especially those that are active in advocating for the provision of accessibility in disability-friendly public facilities, has conducted several advocacies for persons with disabilities in using Mikrotrans public transportation, such as conducting consensus, audits at several bus stops, and testing bus stop designs.